Soil Penetration Resistance in Relation to Depth, Geomorphic Position and Moisture in Wonosari Village, Kendal Regency - Mas Alvy Dwi Sayaza; Abner Atmajendra Waluyaning Jati (Universitas Ibn Khaldun Bogor, 2026)
Soil compaction strongly affects root growth, water infiltration and agricultural productivity. This study analysed the effect of soil depth and geomorphic position on soil penetration resistance, the standard field proxy for compaction, and its relationship with soil moisture in Wonosari Village, Kendal Regency, Central Java. Measurements were made in June 2026 at 47 sampling points using a hand-operated cone penetrometer at four depth intervals (0–10, 10–20, 20–30 and 30–40 cm), with three to four replications per point, together with land morphology classification and soil moisture measurement. Morphology could not be assigned at eight points, so morphology and moisture analyses used 39 points. Predominantly non-parametric methods were applied. Penetration resistance increased consistently with depth, from a mean of 804 kPa in the surface layer to 1,728 kPa at 30–40 cm, while variability was greatest at the surface. The convex/upper class recorded the highest resistance (1,630 kPa) and differed significantly from backslopes (1,112 kPa). No interaction between depth and morphology was detected, and no significant relationship with soil moisture was found, although statistical power was low in both cases. Because bulk density was not measured, conclusions about compaction remain inferential. Landscape position should be considered when preparing land for agroforestry development.